Effectiveness of betta splendens as a biological predatory against aedes aegypti larvae - Permata, Saniya Hanum; Yotopranoto, Subagyo; Kusmartisnawati, Kusmartisnawati (Folia Medica Indonesiana, 2016)
Dengue Hemorrhagic Fever (DHF) is caused by dengue virus and transmitted by Aedes aegypti mosquito. There are several fish species known to be used as a biological predator of Aedes aegypti larvae, such as Betta splendens. The purpose of this study was to examine Betta splendens as a biological predator of Aedes aegypti larvae. The larvae used were in the fourth stage. The Betta splendens consisted of four replicate groups, 3 and 6 months male age group, and 3 and 6 months female age group. The effectiveness rate of predation was only counted based on the speed of eating of 25 larvae in the aquarium containing 3 liters of water. Statistical test was performed with Annova with the parameters fish body weight and time to prey. The longest mean of preying time was found in 3 months aged male fish group (mean body weight = 1.474 grams), with a mean time of prey = 153.80 seconds. The shortest mean preying time was found ini 6 months aged female fish group (mean body weight = 2.566 grams), with a mean time of prey = 142.41 seconds. In conclusion, female 6 month-aged fish with highest mean body weight is most effective againts Aedes aegypti larvae. The body weight can affect the speed of preying, but body weight is only one of some variables that affect the speed and effectiveness beside gender and age of Betta splendens.